Sub-Synchronous Oscillation Analysis and Suppression in Hybrid Wind Farm - Yun Wang; Mingkun Liang; Feilong Xie; Chaoyang Long; Rong Yang (Energies)
This paper investigates the stability mechanisms and suppression strategies for sub-synchronous oscillations (SSOs) in hybrid wind farms (HWFs) consisting of doubly-fed induction generator (DFIG) and permanent magnet synchronous generator (PMSG)-based wind turbines. To address the challenges in mitigating SSOs due to the complex interactions between the generators in hybrid wind farms, as well as external and parameters disturbances, a state-space model of the HWF is developed to capture the impact of external disturbances and parameter uncertainties on system dynamics. Through eigenvalue and participation factor analyses, this paper examines the effects of uncertainties in voltage control parameters, grid line series compensation, and the fluctuating power outputs of DFIGs and PMSGs on SSO behavior. A robust SSO suppression controller based on H∞ theory is proposed, demonstrating a substantial reduction in harmonic distortion and improved settling time compared to conventional control strategies under varying disturbances. The simulation results show that the proposed controller significantly enhances the system’s resilience to disturbances and uncertainties, effectively mitigating SSO and improving overall system stability.